A ROS‐Responsive Dual‐Targeting Drug Nanocarrier Serving as a GSI Synergist and Ferroptosis Sensitizer for T‐Cell Acute Lymphoblastic Leukemia - Ruinan Jia; Yang Liu; Jilong Xiao; Yuan Xia; Xin Zhao; Huixian Ma; Jingjing Ye; Zhiyue Zhang; Tao Sun; Chunyan Ji (Advanced Science)
Abstract T‐cell acute lymphoblastic leukemia (T‐ALL) is a highly aggressive hematological malignancy for which targeted therapies remain underdeveloped. Oncogenic mutations in Notch1 occur in up to 75% of T‐ALL patients. Although γ‐secretase inhibitors (GSIs) can block Notch1 activation, their clinical application is limited by side effects and reduced sensitivity. Here, a self‐assembling, reactive oxygen species (ROS)‐responsive nanotherapeutic strategy—PHD/G‐NPs—co‐loaded with GSI and controlled released dihydroartemisinin (DHA), and modified with a CD38 antibody is reported. The CD38 antibody specifically targets T‐ALL cells, while GSI selectively inhibits Notch1, resulting in a dual‐targeting approach. GSI is released first, inhibiting Notch1 activation and inducing the death of a subset of T‐ALL cells. To eliminate semi‐quiescent T‐ALL cells that escape initial therapy by elevating ROS levels, a ROS‐sensitive DHA delivery system is employed to enhance ferroptosis and boost GSI efficacy. After elucidating the mechanism of action of PHD/G‐NPs in T‐ALL cells, PHD/G‐NPs are combined with αPD‐1, which triggers an anti‐tumor immune response in vivo. This dual‐targeting strategy using CD38‐modified PHD/G‐NPs enables controlled drug release, enhances ferroptosis, mitigates GSI‐induced gastrointestinal toxicity, and improves therapeutic efficacy. This nanomedical approach offers a novel strategy for targeted T‐ALL treatment.